Comparison of bioaerosol sampling methods for swine barns - B Z Predicala; J E Urban; S B Jerez; Ronaldo G Maghirang; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2001)
Two bioaerosol sampling methods (Andersen sampler and filtration sampler) were compared. The two samplers were used to assess the bioaerosol loads in two swine finishing barns. They were similar in terms of the species of microorganisms sampled. The persistent strains of microorganisms were various species of the following genera: Staphylococcus, Pseudomonas, Bacillus, Listeria, Enterococcus, Nocardia, Lactobacillus, and Penicillium. However, the use of Andersen sampler resulted in significantly higher bioaerosol concentrations than the filtration sampler. Thus, it appears that filtration sampling can be used for a qualitative survey of bioaerosols in swine barns while the Andersen sampler is suitable for both quantitative and qualitative assessments.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Airborne microorganisms; Bioaerosol sampling; Swine housing